(untitled) (Academia Journal of Medicine, 2026)
Background: Saliva plays a crucial role in maintaining oral health by neutralizing acids, providing antimicrobial action, and aiding in mechanical cleaning. Chewing sugar-free gum has been suggested to stimulate salivary flow and reduce plaque accumulation, but clinical evidence remains limited. Aim: To evaluate the effect of sugar-free chewing gum on salivary flow rate and dental plaque levels in healthy adults. Materials and Methods: A Clinical trial was conducted on 40 healthy adult volunteers. Participants were instructed to chew sugar-free gum for 10 minutes, three times daily, after meals for 7 days. Unstimulated and stimulated salivary flow rates were measured at baseline and after the intervention. Plaque levels were assessed using the Plaque Index (Silness & Löe) at baseline and post-intervention. Data were analyzed using paired t-tests, with significance set at p < 0.05. Results: Chewing sugar-free gum significantly increased stimulated salivary flow rates (p < 0.01) and led to a significant reduction in plaque scores (p < 0.05) compared to baseline. Conclusion: Sugar-free chewing gum effectively stimulates salivary flow and reduces plaque accumulation. It can be recommended as an adjunct to routine oral hygiene, particularly in individuals with low salivary flow or at high risk of dental caries.